2012
DOI: 10.1073/pnas.1217103109
|View full text |Cite
|
Sign up to set email alerts
|

Connexin45 modulates the proliferation of transit-amplifying precursor cells in the mouse subventricular zone

Abstract: Connexins have been implicated in the regulation of precursor cell migration and proliferation during embryonic development of the mammalian brain. However, their function in postnatal neurogenesis is unclear. Here we demonstrate that connexin (Cx) 45 is expressed in transit-amplifying cells and neuroblasts in the postnatal subventricular zone (SVZ) and modulated the proliferation of SVZ-derived precursor cells in vivo. Thus, overexpression of Cx45 by retroviral injections increased the proliferation of Mash-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…The molecular basis for the observed hyperproliferation in the Cx30A88V mouse line and the palmoplantar hyperkeratinization of Clouston syndrome patients may be similar to the mechanisms suggested for Cx45 hemichannels in the subventricular zone of the brain [22]. For example, an enhanced ATP release by ‘leaky’ Cx30A88V hemichannels could lead to the activation of Ca 2+ dependent kinases via binding to Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The molecular basis for the observed hyperproliferation in the Cx30A88V mouse line and the palmoplantar hyperkeratinization of Clouston syndrome patients may be similar to the mechanisms suggested for Cx45 hemichannels in the subventricular zone of the brain [22]. For example, an enhanced ATP release by ‘leaky’ Cx30A88V hemichannels could lead to the activation of Ca 2+ dependent kinases via binding to Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 59%
“…It has been suggested that Cx45 hemichannels, which are expressed in the transit‐amplifying cells of the subventricular zone of the brain, stimulate proliferation by releasing ATP. The authors propose a model involving the binding of released ATP to P2X receptors, which leads to Ca 2+ release and modulation of cell cycle re‐entry via ERK1/2 and cyclin D [22]. Of note, a recent publication showed that air‐stimulated ATP release in keratinocytes can be blocked by hemichannel inhibitors and therefore indicates that connexin hemichannels are involved in ATP release from keratinocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…This includes a nonspecified P2X receptor in nestin‐GFP‐positive adult hippocampal progenitors and the P2X7 receptor in nestin‐EGFP‐positive precursor cells of the mouse SVZ . A slight increase in BrdU incorporation in the hippocampal granule cell layer was observed in P2rx7 KO mice and nonspecified P2X receptors have been inferred in the stimulation of BrdU incorporation in the SVZ of organotypic brain cultures from P15 mice . In contrast, in cultured fetal or adult neural progenitor cells activation of the P2X7 receptor induced cell death.…”
Section: Discussionmentioning
confidence: 97%
“…Extracellular ATP induces receptor‐mediated Ca 2+ fluctuations in ventricular zone precursors and facilitates progenitor cell proliferation and migration within the developing cortex . Additional studies on the adult SVZ or the adult hippocampus in situ or on organotypic cultures of the SVZ further provide evidence that ATP or the ADP analog adenosine 5′‐ O −2‐thiodiphosphate (ADPβS) can promote progenitor cell proliferation in the adult.…”
Section: Introductionmentioning
confidence: 98%
“…While the HC blocker lanthanium did not affect the migration process [182], it did completely abrogate NPC proliferation in the postnatal SVZ. The latter process relied on Cx45-mediated ATP release and calcium signaling [184]. A similar mechanism was suggested to underlie the role of Panx1 channels in postnatal NPC proliferation [185].…”
Section: General Concepts Of Connexin and Pannexin Signalingmentioning
confidence: 91%